Altered regulatory properties of human cardiac troponin I mutants that cause hypertrophic cardiomyopathy. - Elliott, K; Watkins, H; Redwood, C (2000)
Cardiac troponin I (cTnI) is the inhibitory component of the troponin complex and is involved in the calcium control of heart muscle contraction. Recently, specific missense mutations of the cTnI gene (TNNI3) have been shown to cause familial hypertrophic cardiomyopathy (HCM). We have analyzed the functional effects of two HCM mutations (R145G and R162W) using purified recombinant cTnI. Both mutations gave reduced inhibition of actin-tropomyosin-activated myosin ATPase, both in experiments using cTnI alone and in those using reconstituted human cardiac troponin under relaxing conditions. Both mutant troponin complexes also conferred increased calcium sensitivity of ATPase regulation. Studies on wild type/R145G mutant mixtures showed that the wild type phenotype was dominant in that the inhibition and the calcium sensitivity conferred by a 50:50 mixture was more similar to wild type than expected. Surface plasmon resonance-based assays showed that R162W mutant had an increased affinity for troponin C in the presence of calcium. This observation may contribute to the increased calcium sensitivity found with this mutant and also corroborates recent structural data. The observed decreased inhibition and increased calcium sensitivity suggest that these mutations may cause HCM via impaired relaxation rather than the impaired contraction seen with some other classes of HCM mutants.